Association of Valdecoxib, a Nonsteroidal Anti‐Inflammatory Drug, with Human Serum Albumin1. (16th September 2013) - Encinas, Maria V.; Lissi, Eduardo; Vergara, Claudio
Abstract: Valdecoxib addition quenches the intrinsic human serum albumin (HSA) fluorescence. This allows an evaluation of the drug–protein association. However, both the number of binding sites and their affinity for the drug depend upon the methodology employed for their evaluation and the employed protein concentration. In this work, we measured the effect of valdecoxib on HSA fluorescence yield over a wide range of experimental conditions and discuss the validity of the binding parameters derived from the different data treatments: Stern–Volmer, Scatchard, double logarithmic, quadratic equation, Benesi–Hilderand, and Encinas–Lissi. It is proposed that a combination of Encinas–Lissi and Scatchard treatments of the data renders the most reliable results. From these data, it is concluded that HSA presents three high‐affinity binding sites for valdecoxib ( K as = 4.5 × 10 4 m −1 ) and several secondary sites of smaller activity. Abstract : Valdecoxib addition quenches the intrinsic fluorescence of HSA. The values obtained for the binding constant and the number of binding sites depend on the treatment of the fluorescence data. The most reliable procedure is the treatment of data using a combination of the Scatchard equation and data obtained at different protein concentrations.